PERAN ORGANISASI INTERNASIONAL DAN REGIONAL DALAM MENANGGULANGI HUMAN TRAFFICKING - Hartana; Desak Ketut Alit Apryani (Universitas Pendidikan Ganesha, 2021)
This article discusses the role of international and regional organizations in tackling human trafficking. The type and research approach used by the author in this study is normative juridical. A paper that is prepared based on the main legal material by examining theoretical aspects, concepts, legal principles taken from laws and regulations, court decisions. The data sources in this study were through several data collection methods, namely library research by finding out, understanding, and studying book references, browsing the internet, articles, and literature related to systems analysis. Globalization has so influenced the development of the international world that it is very closely related and inseparable. On the negative impact, there is a desire or an urge for the community to take action or action regarding human trafficking which can be called human trafficking. Human trafficking is among women. Apart from women, there are also men who become human traffickers. The international organization for migration is an international organization that has associations from countries in the international world, of course these countries have succeeded in having an official international organizational structure. Of course, this organization is an official organization that has a special desire, namely to overcome various incidents in the countries of its association, namely to overcome human trafficking incidents.